Positive verbal reinforcement in mathematics education (مجلة الواحات للبحوث والدراسات, 2023)
Abstract:    The Current Study Aimed To Reveal The Most Important Process In Educational Processes Represented In Positive Verbal Reinforcement And Its Impact On Mathematics Education That Is, What The Teacher Uses To Ask Questions And The Diversity In Types Of Reinforcement, As Well As The Use Of Types Of Communication, Whether Verbal Or Non-Verbal, That Stimulate Students' Motivation Towards Learning, And Works To Form Positive Attitudes Towards The Subject. Mathematics Was Chosen Because It Is A Subject That Many Students Struggle To Understand, And This Is Due To Its Degree Of Difficulty, And Sometimes To The Poor Relationship Between Mathematics Teachers And Students. Does Positive Verbal Reinforcement Affect The Formation Of The Learner’s Personality And Identify Positive Attitudes Towards Learning? Keywords: Positive Verbal Reinforcement, Mathematics Education